Building Customer Relationship Management And Financial Reporting Assistance For Retail Enterprises - Iwan Sugianto; Mohamad Nazirwan; Lati Sari Dewi; Siti Amirah Makarim; Sani Haryati; Galih Mauladin Putra; Syahdan Hakiki (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
Retail businesses within pesantren environments face unique challenges, particularly in maintaining consistent customer engagement and managing financial records. This community service initiative, conducted by lecturers from STIE Latifah Mubarokiyah (STIELM), aimed to enhance the managerial capacity of retail business units under the Suryalaya Islamic Boarding School by developing Customer Relationship Management (CRM) strategies and providing technical assistance in financial report preparation. The activity employed a participatory and hands-on learning approach. Thirty participants from pesantren-affiliated retail businesses joined the sessions, which covered CRM principles, customer loyalty programs, and basic bookkeeping. Practical outputs included the formulation of customer service guidelines and structured income-expenditure records. Evaluation results indicated that 87% of participants gained new insights and expressed confidence in applying CRM techniques and financial recording practices. This initiative has laid the groundwork for more structured retail business management in pesantren-based enterprises.